Genetic variant rs16430 6bp > 0bp at the microRNA‐binding site in TYMS and risk of sporadic breast cancer risk in non‐hispanic white women aged ≤55 years. Issue 4 (26th October 2013) - Guan, Xiaoxiang; Liu, Hongliang; Ju, Jingfang; Li, Yangkai; Li, Peng; Wang, Li‐E; Brewster, Abenaa M.; Buchholz, Thomas A.; Arun, Banu K.; Wei, Qingyi; Liu, Zhensheng
Abstract Thymidylate synthase (TYMS) is involved in the folate metabolism and provision of nucleotides needed for DNA synthesis and repair. Thus, functional genetic variants in TYMS may alter cancer risk. In the study, we evaluated associations of three germline variants (rs2790 A > G, rs16430 6 bp > 0 bp, and rs1059394 C > T) in the predicted miRNA‐binding sites of TYMS with risk of sporadic breast cancer in non‐Hispanic white women aged ≤55. We found that carriers of the rs16430 0 bp variant allele had an increased risk of breast cancer [adjusted odd ratio (OR) = 1.37, 95% confidence interval (CI): 1.08–1.73; P = 0.010], compared with carriers of the 6 bp/6 bp genotype. This increased risk was more evident in older subjects (OR = 1.47, 95% CI = 1.06–2.03, P = 0.022), never smokers (OR = 1.67, 95% CI = 1.23–2.25, P < 0.001), never drinkers (OR = 1.44, 95% CI = 1.01–2.05, P = 0.043), and estrogen receptor‐positive patients (OR = 1.46, 95% CI = 1.11–1.92, P = 0.006), regardless of tumor stages. The results are consistent with the functional analyses of rs16430 as previously reported, which showed that the 0bp allele had a decrease in both luciferase activity by ∼70% and mRNA levels by ∼50% compared with the 6bp allele. Additionally, the rs16430 variant was predicted to influence the binding activity of miR‐561. Taken together, these findings indicate that the TYMS rs16430 may contribute to the etiology of sporadic breast cancer in non‐Hispanic white women aged ≤55 yr. Further validation in large population‐based or cohort studies is needed. © 2013 Wiley Periodicals, Inc.